2023
DOI: 10.1108/jmtm-08-2022-0307
|View full text |Cite
|
Sign up to set email alerts
|

Supply chain resilience and performance of manufacturing firms: role of supply chain disruption

Abstract: PurposeThe current study sought to investigate the moderating effect of supply chain disruptions (SCD) (supply chain – supply disruption, catastrophic disruption and infrastructure disruption) on the relationship between supply chain resilience (SCR) and supply chain performance (SCP) of manufacturing firms in Ghana.Design/methodology/approachThe quantitative research approach and explanatory research designs were utilised. A sample of 345 manufacturing firms were drawn from a population of 2,495 manufacturing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 58 publications
2
23
0
Order By: Relevance
“…Cross-loading above 0.7 indicates that all indicators with different constructs contribute well to measuring this variable [25]. Cronbach alpha, rho_A, and Composite reliability (CR) values above 0.7 indicate a high level of consistency between indicators in measuring their variables [26]. A value of AVE larger than 0.5 indicates that most of the variance of the indicators has been explained through the variables themselves, which is further proof of the high quality of the measurements [27].…”
Section: Resultsmentioning
confidence: 99%
“…Cross-loading above 0.7 indicates that all indicators with different constructs contribute well to measuring this variable [25]. Cronbach alpha, rho_A, and Composite reliability (CR) values above 0.7 indicate a high level of consistency between indicators in measuring their variables [26]. A value of AVE larger than 0.5 indicates that most of the variance of the indicators has been explained through the variables themselves, which is further proof of the high quality of the measurements [27].…”
Section: Resultsmentioning
confidence: 99%
“…Change is facilitated by temporal linkages between institutional projects and vertical linkages between institutional projects and sector-level development programs (Pizzi et al, 2023). Hamidu et al (2023) examined the moderating effect of supply chain disruption on the relationship between supply chain flexibility and supply chain efficiency for manufacturing firms in Ghana and showed that SCR has a significant positive effect on SCP. Second, the authors found sufficient evidence that SCD has a significant positive moderating effect on the relationship between SCR and SCP, except for supply chain disruption, which had a negative effect (Patidar et al, 2022).…”
Section: Institutionalization (Inst) and African Continental Free Tra...mentioning
confidence: 99%
“…SCR originally referred to the ability of a supply chain to recover after a disruption and appears to have been adopted from engineering (Nikookar and Yanadori, 2021). In related study, Hamidu et al (2023) examined the moderating effect of supply chain disruption on the relationship between SCR and SCP for manufacturing firms in Ghana and showed that SCR has a significant positive effect on SCP. Second, the authors found sufficient evidence that SCD has a significant positive moderating effect on the relationship between SCR and SCP.…”
Section: Supply Chain Resilience (Scr) and African Continental Free T...mentioning
confidence: 99%
“…A plethora of studies have envisaged that SCR is a crucial factor influencing supply chain performance (SCP) (Chowdhury et al ., 2019; Ekanayake et al ., 2021; Gu et al ., 2020; Hamidu et al ., 2023; Hasani and Khosrojerdi, 2016; Mandal et al ., 2016; Piprani et al ., 2020; Wong et al ., 2020; Zhang et al ., 2021). However, prior studies are silent on the role technological innovation plays in intervening or enhancing the relationship between SCR and SCP (see, Parast et al ., 2019; Sabahi and Parast, 2020; Yu et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Supply chains compete with one other and support environmental sustainability at the same time, according to Blackwell and Blackwell (1999). For this reason, supply chain management development and improvement have received a lot of attention from academics and business professionals with the aim of minimizing supply chain disruption (Hamidu et al, 2022(Hamidu et al, , 2023. This notion is referred to as supply chain resilience (SCR).…”
Section: Introductionmentioning
confidence: 99%